Post-traumatic stress and cancer: Findings from a cross-sectional nationally representative sample. (June 2019) - Kaster, Tyler S.; Sommer, Jordana L.; Mota, Natalie; Sareen, Jitender; El-Gabalawy, Renée
Highlights: Trauma exposure and post-traumatic stress disorder (PTSD) were associated with greater odds of cancer. For trauma exposed respondents, the odds of cancer varied by sex and cancer diagnosis. Illness as the index/worst trauma among those with PTSD was associated with greater odds of cancer. Abstract: Objective: Trauma and post-traumatic stress disorder (PTSD) have been associated with a variety of physical conditions; however, their relationship with cancer is unclear. Methods: Using the cross-sectional 2012–2013 National Epidemiologic Survey on Alcohol and Related Conditions (NESARC-III; N = 36, 309), we examined the association between trauma, PTSD and cancer (breast, gastrointestinal, 'other', and 'any'). Respondents were categorized into three groups: no-trauma, trauma-exposed, and PTSD using DSM-5 criteria. We conducted cancer- and sex-stratified regression analyses to examine the relationship between PTSD and cancer using the non-trauma exposed group as the reference. Results: Cancer prevalence was significantly greater in PTSD than trauma-exposed and no-trauma exposed respondents, and greater in trauma-exposed than no-trauma exposed respondents. After adjusting for covariates, odds of cancer were significantly greater in PTSD compared to non trauma-exposed respondents for 'any' cancer (adjusted odds ratio [AOR]: 2.99; 95% CI=[2.31, 3.88], gastrointestinal (GI) cancer (AOR: 17.48; 95% CI=[8.09, 37.77]), and 'other' cancer (AOR: 3.21; 95% CI=[2.41, 4.27]). Breast cancer was non-significant. Although both males and females with PTSD had significantly increased odds of 'any', GI, and 'other' cancer, differential findings emerged across sexes for those who were trauma exposed, compared to non-trauma exposed. Conclusion: Traumatic exposure and PTSD appear to be associated with cancer. The comorbid relationship between traumatic exposure, PTSD and cancer differs by cancer type and sex.